Coop revolution : 7 rules for collaborative game design - GSummit (2014 : San Francisco, Calif.); Kim, Amy Jo; Safari eBooks ([Place of publication not identified] : FORA.tv, 2014)
"Games are everywhere--and everyone's a gamer. Yet most people's assumptions about gaming and gamification revolve around competitive, zero-sum experiences. The next wave of gaming innovation is coming from indies, outsiders and non-gamers--and they're crafting collaborative systems where people WIN TOGETHER and grow the pie for everyone. What market trends are driving this change? Which influential games and services are leading the way? Come learn the secrets behind Coop hits like Minecraft, Journey, Foldit, Portal, Team Fortress, Left4Dead, Nike+, Youtube, and Kickstarter. Discover the 7 rules for collaborative design that propelled these projects--and walk away with ideas and inspiration for how to apply Coop thinking to your next project. Amy Jo Kim Creative Director, Shufflebrain."--Resource description page.
Title from resource description page (Safari, viewed January 29, 2016).
Presenter, Amy Jo Kim.
Keywords: Games -- Design and construction; Cooperation; Electronic books